Characteristics Generation Traffic Patterns and Movement in Residential Area (Case Study Way Kandis Residential Bandar Lampung) - Fery Hendi Jaya; Juniardi JUNIARDI (International Conference on Engineering and Technology Development (ICETD), 2013)
Prospectus population growth in urban areas is growing rapidly due to the process of human activity, in conjunction with an increase in their subsistence efforts. The most important point that is on the rise residential transportation occurs. Housing is a basic need that must be met in addition to food and clothing, housing placement for the residents of the area will stimulate the movement patterns of the population as well as being the dominant factor will cause a rise of transport traffic on the road network in its path. Those factors that arise due to the influence of family characteristics such as the number of households, number of family members, family members aged> 7 years, work, school, income, vehicle ownership. If this is not observed and handled in particular will result in a level of service characterized by decreased traffic congestion, air pollution, traffic violations, ethical decline in travel, especially economically unprofitable. Therefore, the problems and the further development of the Area Housing Way Kandis Bandar Lampung to improve services in the emerging field of transport, traveling population of 694.71 Total Trip / day may affect the occurrence of traffic jams on the main door Jl. Ratu Dibalau Toward By Pass (towards T.Karang) of 47.87%, 23.53% passed Jl. Ratu Dibalau Toward By Pass (right Rajabasa), 16.63% passed Jl. Damar Island towards Sukarame (two- lane way halim), 7.91% pass through Jl. Damar Island to Teak Mulyo (direction metro) and 4.06% across Jl. Damar Island towards Sukarame (left Panjang). The number of trips that occur depending on the activities of people doing activities with different interests, calculations done indirectly because of the difficulty of calculating the movement or travel. Indirect calculations using an analytical model that results can be close to reality, traffic generation model is caused by the movement of the Perum Way Kandis Bandar Lampung is Y = 2.775 to 0.135 X1-0, 098 +0.179 X2 +0.035 X3 +0.094 X4 +0.120 X5 X6 +0.043 X7, from the equation that the effect on the character of the family who have aged> 7 years at 96.63%. To get an idea of traffic fluctuations that occur, enumeration traffic (Traffic Counting), the exit 3 for 2 (two) days, ie Wednesday that representing the working day and day of the week that represents a holiday. The calculation is performed on traffic coming out of the Housing Kandis Way Bandar Lampung, counting results showed peak time occurred in the morning at 07:00 to 8:00 and in the afternoon at 4:00 p.m. to 5:00 p.m., and holidays at 08:00 to 9:30 pm.